Washington view: Federal stimulus packages: Act II. (December 2021) - Ferguson, Maria
As education leaders are making plans for how to use American Rescue Plan funds, Maria Ferguson considers what lessons they might learn from the American Recovery and Reinvestment Act in 2009. Like the tranches of funding being provided to schools as COVID relief, the ARRA funds were meant to help schools grapple with a national crisis, in that case the Great Recession. To receive funds, states had to commit to certain reforms that aligned with President Barack Obama's education agenda. However, the funds were not enough to enable state, district, and school leaders to accomplish the desired goals, and the political heat generated by the Common Core State Standards didn't help. Today's funds come with more flexibility than in the ARRA era, but, once again, money may not be enough to accomplish what's needed .